LA LECCIÓN DE MAQUIAVELO. LOUIS ALTHUSSER HACIA UNA RESEMANTIZACIÓN DE LA POLÍTICA. - Dominguez, Esteban (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
This paper intervenes in the scope of contemporary political theory, trying to indicate Louis Althusser as an important author for the contemporary question about politics. It aims to explore the althusserian reading about Machiavelli, outlining two ideas to develop preliminarily in these pages. First, answering why there is a recurrence to Machiavelli in Althusser’s work. We will defend that the reading of Machiavelli, over-determinates Althusser’s intervention, adding ‘new’ themes and updating ‘old’ questions of althusserianism. Thereby, a lecture like this one would allow recovering in a specific way certain legacy of the author. treating the problem of the beginning in politics in its impossible conditions –between the eternal repetition of the same and the absolute contingency to come-, we will indicate what Althusser came through with Machiavelli: the possibility of expanding the potential of sense of politics versus the ones that try to reduce it in its concept and effects. As product of this study we will be indicate how Althusser’s question about politics can be considered in a post-foundational theoretical horizon.